An investigation of leg and shoulder muscle strength ratios of elite female volleyball players - Cengiz Akarcesme; Zait Burak Aktug; Hasan Aka; Serkan Ibıs (Türk Spor ve Egzersiz Dergisi)
Providing muscular strength balance is an important factor in both improving sport performance and preventing sports injuries. The aim of the current study is to determine the leg and shoulder muscle strength ratios of elite female volleyball players. 14 elite voluntary female volleyball players were included in the study. Dominant (D) and nondominant (ND) knee and shoulder muscle strength ratios of volleyball players who participated in the study were determined by isokinetic dynamometer at 60 ° s-1 and 180 ° s-1 angular speeds. Bilateral force differences (BLD), leg hamstring / quadriceps ratio (H/Q) and shoulder external / internal ratio (E/I) averages and standard deviations were determined for the leg and shoulder muscles after the obtained data were applied to the SPSS program. Statistical analysis revealed that the H/Q ratio was low and the E/I ratio was high at 60°s-1 and 180°s-1 angular velocities. It was also been determined that the BLD of the shoulder muscles was high while the BLD of the leg muscles was at the desired level at 60°s-1 and 180°s-1 angular speeds. As a result, the volleyball players participating in the study seem to have lower leg muscle strength and lower H/Q ratio. Furthermore, although it is thought that more work is done with the upper extremity in the volleyball, it can be said that lower extremity force development should not be ignored since it is a well-known fact that the entire body is carried by the lower extremity to change rapidly.